Uso e ocupação do solo nas margens da Rodovia BR- 235/SE - Caldas Júnior, Eldonor Targino (2017)
The problem of the use of the ground is an important point of discussion in the present time, to the extent that the anthropic actions advance on the environment. In recent years, we have experienced considerable growth in Brazil's infrastructure, especially in the construction of highways, a fact that has caused socio-economic and environmental changes in the affected regions. In this context, the disorderly and illegal use of domain strips, popularly called road borders, emerged. The general objective of this research was to evaluate the causes and consequences of the use of these marginal areas in the road stretch between kilometer 0.0 and kilometer 114.8 of BR-235 in Sergipe, based on current legislation and surveys Field tests. The methodological procedures related to this research included describing the occupation process; To analyze the community's perception regarding the use of public lands, through field interviews; To evaluate aerophotogrammetric data of the headquarters of the municipalities that are part of the study area, aiming to establish alternatives to mitigate the problem exposed. The results revealed the environmental compromise of the border areas along the highway, a circumstance observed in the aerial images collected from the UAV (Unmanned Aerial Vehicle) and the topographic data of the study area. On the other hand, the data collected in interviews pointed out that the practice of using the domain strip is permanent and progressive, illegal, without inspection of public entities and harmful to road engineering. It is imperative that the recommendations proposed by this research be supported and adopted by public entities and the local community, such as the improvement of the municipal plans to regulate the construction of monuments or public facilities in the vicinity of roads and the restoration Monitoring and oversight of management bodies to prevent the advance of invasions.